The Effect of Liquidity and Size of The Company Towards Company Tax Aggressiveness - Sapta Setia Darma (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
This study aims to find empirical evidence of the effect of liquidity and firm size on the tax aggressiveness of companies listed on the Indonesia Stock Exchange for the period 2012-2017. The study was conducted on 17 food and beverage companies listed on the Indonesia Stock Exchange, using a purposive sampling method through predetermined criteria. The data obtained were 7 companies that were used as research samples with observations over the six years 2012-2017, furthermore total observations were as many as 42 samples. The data used are secondary data, namely the company's annual financial statements for the period 2012-2017. Data analysis method used in this study is normality analysis. The results showed that: liquidity has no significant effect on corporate tax aggressiveness, while company size has a significant effect on corporate tax aggressiveness as well as liquidity and company size has a significant effect on corporate tax aggressiveness.